Sarah of the Sahara: A Romance of Nomads Land - Chappell, George S. (George Shepard), 1877-1946 (Salt Lake City, UT : Project Gutenberg, 2021)
"Sarah of the Sahara: A Romance of Nomads Land" by Walter E. Traprock is a novel written in the early 20th century. The story begins with the captivating introduction of Sarah Wimpole, a strong and mysterious woman who captures the heart of the protagonist, Dr. Traprock, a nomadic sheik. As their lives intertwine amid the exotic backdrop of the desert, themes of love, adventure, and the clash of cultures unfold, drawing readers into a world of romance filled with danger and intrigue. The opening portion of "Sarah of the Sahara" introduces Dr. Traprock's passionate encounter with Lady Sarah Wimpole at Cannes, where her striking presence intrigues him. Traprock, an explorer at heart, is immediately captivated, abandoning his previous plans for adventure on whims of love and fate. Their second fateful meeting at a casino in Monte Carlo escalates the tension as Traprock finds himself entangled in not only passion but impending danger when he learns of attempts to rob Lady Sarah. As the narrative progresses, Traprock$1 (Bs longing for Sarah leads him on a daring pursuit into the deserts of North Africa, where he intends to win her heart against the perils posed by her arrogant husband and the notorious bandit Azad. Thus, the stage is set for a captivating tale filled with romance and adventure. (This is an automatically generated summary.)s
Release date is 2021-10-24
Emmanuel Ackerman, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Adventure stories; Man-woman relationships -- Fiction; Egypt -- Fiction; Explorers -- Fiction; Sahara -- Fiction; Burlesque (Literature)